CONSTRUCTION OF LEGAL DISCOVERY BY JUDGES IN SETTLEMENT OF CIVIL MATTERS - Taruna, Bayu Lesmana; Rahman, Sufirman; Nawi, Syahruddin; Husen, La Ode (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The purpose of the study is to analyse the legal findings of judges in resolving civil cases. The research in this dissertation is included in the type of Normative research using a legal material study approach supported by a literature study or literature that is closely related to the object of the study. Based on the results of the study, the researcher can conclude that in the case of the Decision and Determination of the Gorontalo District Court Number: 1 / Pdt.P-Kons / 2023 / PN.Gto Jo. Special Criminal Decision Number 177 / Pid.Sus / 2022 / PN Gto, the construction of the decision that was previously prepared in Concrete since the Legal considerations in the criminal case until it became a norm in the form of a Civil Determination which can be used as a basis for filling the regulatory gap regarding the return of mining evidence in conditions of the absence of rules or regulations that regulate.